Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.13189/aeb.2016.041002
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Employability: A Gap between Perspectives - the Case of Croatia

Abstract: Awareness of the importance of higher education (HE) in the transition to a knowledge-based society is growing in Croatia and universities are increasingly required to produce employable graduates who have attributes, capabilities, knowledge and skills to work successfully, and are able to respond to the changing and complex needs of the labor market. This paper seeks to investigate and compare the importance of skills and attributes which enhance graduate employability, as well as their reception through high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Additionally, Rosenbaum (2012) observed that if students didn't develop basic employability skills before their employment, they might not be able to learn them after they got hired. Since employers are hesitant to invest in training and development after hiring (Kőnig et al, 2016), training and development should be considered an investment in a sustainable future of a burden cost (Kyrieri & Roidou, 2012). This gap can be filled to some extent in case of academic mobility if it aims at employability increase due to professional skills improvement (Kabanbayeva et al, 2019), the same effect can be achieved via students' educational migration (Mishchuk et al, 2019).…”
Section: Employability Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Rosenbaum (2012) observed that if students didn't develop basic employability skills before their employment, they might not be able to learn them after they got hired. Since employers are hesitant to invest in training and development after hiring (Kőnig et al, 2016), training and development should be considered an investment in a sustainable future of a burden cost (Kyrieri & Roidou, 2012). This gap can be filled to some extent in case of academic mobility if it aims at employability increase due to professional skills improvement (Kabanbayeva et al, 2019), the same effect can be achieved via students' educational migration (Mishchuk et al, 2019).…”
Section: Employability Skillsmentioning
confidence: 99%
“…Moreover, employers are concerned with the shortage of employability skills, already demonstrated by the entry-level job applicants as this is considered a global issue (Teng et al, 2019). Despite employability importance, there are discrepancies in the visions on employability skills between higher education students and employers (Kőnig et al, 2016;Ahmad & Pesch, 2017;Singh et al, 2017). The main aim of this study is to analyze higher education students' perspective on employability skills, so we can compare it with the labour market skills demand in order and thus to evaluate the students' knowledge about future job skills as requested by employers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to do this until now scholars conducted surveys primarily among various populations of higher education stakeholders. On a much lesser scale researchers explored employers' expectations regarding the skills of their potential employees investigated employers' satisfaction with graduates' skills (Andrews & Higson, 2008; Piróg, 2016; Kőnig et al, 2016; Nagarajan & Edwards, 2015; Sarkar et al, 2016). Some scholars asked graduates about the usefulness of skills/competences acquired at university for their job seeking efforts (Piróg, 2016; Nagarajan & Edwards, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars asked graduates about the usefulness of skills/competences acquired at university for their job seeking efforts (Piróg, 2016; Nagarajan & Edwards, 2015). Kőnig et al (2016) conducted interviews with academic staff and lecturers regarding their view and reflection on the sought‐after competences of graduates on the labour market. Sarkar et al (2016) have expressed criticism about the usefulness of results obtained via surveys among the above‐mentioned populations for the purpose of redesigning curricula and the concept of study.…”
Section: Introductionmentioning
confidence: 99%
“…Os autores detectaram que os discentes creem ser uma obrigação das universidades a preocupação com a empregabilidade, enquanto os professores acreditam que a formação deve ser para atender à sociedade e não ao mercado. E, por fim, o estudo realizado por Kőnig;Juric;Koprivnjak (2016) concluiu que mais do que a simples formação dos alunos, as capacidades interpessoais é que seriam os requisitos mais relevantes para a empregabilidade dos alunos.…”
Section: Introductionunclassified